Perkembangan Kebijakan Pembelajaran Agama Islam Pada Lembaga Pendidikan di Indonesia - Windy Dian Sari; Akhmad Shunhaji (Alim | Journal of Islamic Education, 2020)
This paper discusses the development of Islamic religious learning policies in educational institutions in Indonesia. The data were obtained by reviewing the literature related to education policy through a descriptive qualitative approach. The results showed that the state's support for fulfilling the needs of Islamic religious learning was increasing. The Indonesian government establishes an Islamic religious learning policy for every Muslim citizen. This policy leads to educational development services through effective Islamic religious education learning. The needs of Muslim students for the development of spiritual potential receive policy support from the government